2019
DOI: 10.1103/physrevaccelbeams.22.020703
|View full text |Cite
|
Sign up to set email alerts
|

Generation of large-bandwidth x-ray free electron laser with evolutionary many-objective optimization algorithm

Abstract: X-ray free-electron lasers (XFELs) are cutting-edge scientific instruments for a wide range of disciplines. Conventionally, the narrow bandwidth is pursued in an XFEL. However, in recent years, the large-bandwidth XFEL operation schemes are proposed for X-ray spectroscopy and Xray crystallography, in which over-compression is a promising scheme to produce broad-bandwidth XFEL pulses through increasing the electron beam energy chirp. In this paper, combining with the beam yaw correction to overcome the transver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Not only can all kinds of RF cavity optimizations be well handled, such as multi-cell cavity 11 and heavy ion cavities 41 , but also other accelerator optimization are principally suitable, like free electron laser 5 , 6 , nonlinear beam dynamics 4 and so on. If we look at optimization designs in other physics fields, such as radio apparatus 42 and structural components of materials 43 , more questions would be solved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only can all kinds of RF cavity optimizations be well handled, such as multi-cell cavity 11 and heavy ion cavities 41 , but also other accelerator optimization are principally suitable, like free electron laser 5 , 6 , nonlinear beam dynamics 4 and so on. If we look at optimization designs in other physics fields, such as radio apparatus 42 and structural components of materials 43 , more questions would be solved.…”
Section: Discussionmentioning
confidence: 99%
“…The field of accelerator can be taken as an example. There are many complex optimization problems that do not have the known optimal solution sets (the Pareto front) in accelerator fields, and good performance has been preliminarily obtained with MOGAs in some of these problems, such as the optimization of lattice 4 , Free Electron Laser 5 , 6 and other accelerator facilities 7 . Designing the shape of radio frequency (RF) cavity is a sort of important problem as well, in which several objectives such as geometric shunt impedance (R/Q), Q factor and shunt impedance (R a ) are optimized simultaneously by tuning the geometric parameters of the cavity.…”
Section: Introductionmentioning
confidence: 99%
“…A priori methods: In the article where NSGA-III was proposed [10], the authors suggested a mechanism to incorporate preferences a priori by filtering the RVs utilized by the method. A similar approach was used by Yan et al [34] and da Silva et al [8,31,30]. Cheng et al [6] proposed an a priori version of NSGA-III that requires the DM to specify a central RV, which is utilized to adapt the complete set of RVs.…”
Section: Related Workmentioning
confidence: 99%
“…With the rapid development of computer science and high-performance cluster, many improved algorithms are accessible and the Non-dominated Sorting Genetic Algorithm III(NSGA-III) is selected to be applied to this beam dynamics optimization strategy. NSGA-III is an evolutionary many-objective optimization algorithm using the reference-point-based non-dominated sorting approach, which keeps it efficient in optimizing more than three objectives simultaneously compared with NSGA-II [42,43,44]. Based on it, the beam dynamics simulation of the injector section is conducted using ASTRA, which is a space charge tracking algorithm widely used worldwide to simulate beam dynamics in injector sections [45].…”
Section: Many-objective Photoinjector Beam Dynamics Optimization For ...mentioning
confidence: 99%